Investment laws, challenges and prospects in Uganda - Asiimwe Jackline (KAS African Law Study Library)
Uganda has an investment regulatory framework in place. However, following the enactment of the Anti Homosexuality Act early 2024, many donors withdrew their financial support for government programs. This has led to high taxes to obtain revenue for financing government activities which has negatively affected both national and foreign investments. This has resulted into closure of some investments, while the remaining ones are struggling to survive. The other challenges include: corruption, lack of financial and technical knowhow, capacity among nationals, lack of law abiding culture and the gaps in the existing legal framework. The study recommends the utilization of existing portals to report corruption; investing in capacity building of nationals; use of the Alternative Dispute Resolution (ADR) at the High Court Commercial Division, and use of the growing market. This study examines the investment laws, points out gaps, challenges, and prospects.